2017
DOI: 10.5935/0101-2800.20170031
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of hemodialysis patients about dietary and fluid restrictions

Abstract: Participants perceived a greater difficulty to control fluid and phosphate intake rather than sodium and potassium, higher perceptions scores were associated with subgroups and with worse control of clinical parameters. Moreover, patients with a greater difficulty to control some dietary item also found harder to control the other ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 0 publications
0
13
0
6
Order By: Relevance
“…Patients on hemodialysis (HD), the most common treatment modality, are required to adhere strictly to treatment regimen namely diet, fluids, medications (phosphate binder), and dialysis therapy [ 6 ]. The most common dialysis prescriptions, however, do not provide adequate phosphate removal [ 7 ], with hyperphosphataemia frequently reported among HD patients [ 8 , 9 , 10 ]. Precise reasons for this gap remain unclear and various factors have been linked to poor phosphate compliance among HD patients including socio-demographic factors [ 11 , 12 ], depression [ 13 , 14 ], social support [ 15 , 16 ], medication adherence [ 11 , 17 , 18 ], nutritional knowledge on phosphorus [ 11 , 19 ], and sleep quality [ 20 , 21 ] with inconsistencies existing [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients on hemodialysis (HD), the most common treatment modality, are required to adhere strictly to treatment regimen namely diet, fluids, medications (phosphate binder), and dialysis therapy [ 6 ]. The most common dialysis prescriptions, however, do not provide adequate phosphate removal [ 7 ], with hyperphosphataemia frequently reported among HD patients [ 8 , 9 , 10 ]. Precise reasons for this gap remain unclear and various factors have been linked to poor phosphate compliance among HD patients including socio-demographic factors [ 11 , 12 ], depression [ 13 , 14 ], social support [ 15 , 16 ], medication adherence [ 11 , 17 , 18 ], nutritional knowledge on phosphorus [ 11 , 19 ], and sleep quality [ 20 , 21 ] with inconsistencies existing [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular mortality has been shown to be 30 times higher among people with end-stage kidney disease (ESKD) than in the general population [4]. Among factors contributing to the abysmal clinical outcomes in these patients, poor adherence to prescribed pharmacologic and nonpharmacologic treatments is a common albeit potentially modifiable problem, not least of which involves adherence to dietary advice provided by dietary counseling, which is one of the cornerstones of nonpharmacologic care for CKD patients [5,6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The dietary modifications such as changes in the energy intake, intake of macronutrients, minerals and fluids can significantly reduce the risk for increased mortality and morbidity. 3 - 5 It has been observed that between 20 - 78% of the patients are non-adherent to diet and fluid restrictions because of the modification in their long-standing individual routine life.…”
Section: Introductionmentioning
confidence: 99%